APPLICATION OF BAT ALGORITHM IN SOLVING NONLIEAR ORDINARY DIFFRENTIAL EQUATIONS - Zaini, Achmad
There are a great variety of linear and nonlinear ordinary differential equation (ODEs) problems. A general formulation is needed to solve this ordinary differential equation independent of their form, order and given conditions. The ODEs are formulated as optimization problem. The Fourier series expansion, collocation method, and optimization method are employed in the formulation of this problem. The optimization method that is commonly used is gradient based method. This method has some weaknesses they are, the objective functions of the problem are required to be differentiable function, it is often trapped in minimum local, and it depend on the first guess point. Nowadays, there are many metaheuristic method which do not depend on the derivative of the objective function. These methods do not guarantee to obtain the exact solution, but produce solution that nearly optimal. In this final project, the author use Bat Algorithm to solve this metaheuristic optimization problem. Bat Algorithm is one of metaheuristic algorithm that is first developed by Xin She Yang in 2010.